2022
DOI: 10.1002/jdd.13086
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of empathy among dental interns and postgraduate students at King Abdulaziz University: A cross‐sectional study

Abstract: Purpose/Objectives Empathetic communication of dentists with their patients is a primary characteristic of their health care. This study aims to evaluate dental students’ empathy levels during the transitional period of internship and postgraduate studies of different specialties at one of the oldest dental schools in Saudi Arabia and explore how this empathy was affected by gender, age, and study duration. Methods In this study, the self‐reported empathy level among the participants was assessed using the Jef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(155 reference statements)
0
0
0
Order By: Relevance
“…The coefficient value for all constructs ranged from 0.795 to 0.858, which was higher than the acceptable limit. The authors of [42] suggested that a value of 0.6 to 0.7 is acceptable, while 0.8 or greater is very ideal. In this study, the coefficient value for performance expectancy was 0.803, the coefficient value for effort expectancy was 0.795, the coefficient value for facilitating condition was 0.858, the coefficient value for deriving attention was 0.813, and the coefficient value for intention was 0.822.…”
Section: Methodsmentioning
confidence: 99%
“…The coefficient value for all constructs ranged from 0.795 to 0.858, which was higher than the acceptable limit. The authors of [42] suggested that a value of 0.6 to 0.7 is acceptable, while 0.8 or greater is very ideal. In this study, the coefficient value for performance expectancy was 0.803, the coefficient value for effort expectancy was 0.795, the coefficient value for facilitating condition was 0.858, the coefficient value for deriving attention was 0.813, and the coefficient value for intention was 0.822.…”
Section: Methodsmentioning
confidence: 99%